Novel synthetic lethality screening method identifies TIP60-dependent radiation sensitivity in the absence of BAF180 - Hopkins, Suzanna R.; McGregor, Grant A.; Murray, Johanne M.; Downs, Jessica A.; Savic, Velibor (DNA repair, 2016)
In recent years, research into synthetic lethality and how it can be exploited in cancer treatments has emerged as major focus in cancer research. However, the lack of a simple to use, sensitive and standardised assay to test for synthetic interactions has been slowing the efforts. Here we present a novel approach to synthetic lethality screening based on co-culturing two syngeneic cell lines containing individual fluorescent tags. By associating shRNAs for a target gene or control to individual fluorescence labels, we can easily follow individual cell fates upon siRNA treatment and high content imaging. We have demonstrated that the system can recapitulate the functional defects of the target gene depletion and is capable of discovering novel synthetic interactors and phenotypes. In a trial screen, we show that TIP60 exhibits synthetic lethality interaction with BAF180, and that in the absence of TIP60, there is an increase micronuclei dependent on the level of BAF180 loss, significantly above levels seen with BAF180 present. Moreover, the severity of the interactions correlates with proxy measurements of BAF180 knockdown efficacy, which may expand its usefulness to addressing synthetic interactions through titratable hypomorphic gene expression.